Sunset Long Shadows: Time, Crime, and Perception of Change - Pavel Jelnov (Institute of Labor Economics (IZA), 2021)
How long survives perception of change after evaporation of the actual change? I investigate the effect of daylight on crime and fear of crime. Forty years of reforms shifted the boundaries between Russian eleven time zones. I find that a permanent switch to a later sunset leads to a two year long decrease in robbery and has no effect on homicide. The magnitude of the effect on robbery is similar to the previous estimates from other countries immediately after daylight saving time transitions. Even though the actual effect lasts two years, women report in a 10-year perspective increased feeling of safety even in darkness. However, men report increased feeling of safety only as long as the actual decrease in robbery persists.
Keywords: J18; 330; crime; daylight saving time; fear of crime; homicide; robbery; Russia; time zones